ANALYSIS STUDY OF THE INCIDENCE OF UNDER-FIVE NUTRITIONAL STATUS FAILURE BASED ON ANTHROPOMETRIC COMPOSITE INDEX (CIAF) IN WEST SUMATRA PROVINCE. - Sulung, Neila; Hasnita, Evi; Mariyana, Rina; Syafriyanti, Mega (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
WHO in 2020 estimates that 52 million children under 5 years are underweight, 17 million people are very thin and 155 million are short, while 41 million people are obese . About 45% of deaths among children under 5 years of age are related to malnutrition. For determine nutritional status child used index anthropometry Composite Index of Anthropometric ( CIAF ) that is index combining anthropometry _ three index ; weight / age , height / age , and weight / height . Study This aim For know the determinants of nutritional status child based on Composite Index of Anthropometric ( CIAF) in West Sumatra Province .Method : This type of research is quantitative with a cross research design s sectional was carried out in May-August 2018. The study population was 9,164 children aged 24-59 months with sample of 801 children aged 24-59 months in 10 districts and cities in West Sumatra Province . Data analysis used Chi square statistical tests and regression logistics .Research results : Determinants related to children's nutritional status based on CIAF in 10 districts and cities in West Sumatra Province is maternal education with ( p : 0.024 ; OR : 0.588 (0.37-0.93) ) , economic status (p: 0.003, OR: 0.492 (0.31-0.78)), infectious diseases ( p : 0,000 5 ; (OR : 0, 298 (0.21-0.43) ) and food diversity ( p : 0.000 5 ; OR : 0, 2 17 (0.14-0.33) ) . Conclusion:  The most dominant factor influencing children's nutritional status based on CIAF is mother's education . It is hoped that posyandu cadres will be able to provide education regarding child nutrition to mothers so that children's health can be monitored for nutrition to report child nutrition problems.